The Receptor for the CD200 Tolerance‐Signaling Molecule Associated with Successful Pregnancy is Expressed by Early‐Stage Breast Cancer Cells in 80% of Patients and by Term Placental Trophoblasts. (24th May 2015) - Clark, David A.; Dhesy‐Thind, Sukhbinder; Arredondo, Jorge L.; Ellis, Peter M.; Ramsay, Jennifer A.
<x xml:space="preserve">Abstract</x> Problem The CD200 tolerance‐signaling molecule that is expressed by a wide variety of tissues, including placental trophoblast and epithelial tumor cells, lacks an intracytoplasmic tail and must act by binding to CD200 receptors that have a limited expression on lymphomyeloid cells. This binding can inhibit inflammation and NK cells, promote macrophage secretion of indoleamine‐2, 3 dioxygenase (IDO), and promote generation of Treg cells. Recently, CD200R1 was reported on human first trimester placental villous trophoblast cells. CD200R1 has not been described on malignant tumor cells. As malignant tumor cells exhibit a number of characteristics of trophoblast, is CD200R1 expressed? Method of study Affinity‐purified rabbit polyclonal antibodies to CD200 and CD200R1 were used to immunostain tissue blocks available from cases in a previous cross‐sectional study of Stage 1‐IIIA human breast cancer cases and term placental trophoblast. Results Affinity‐purified anti‐CD200R1 stained primary breast cancer cells and term placental villous trophoblasts. Tumor cells were also stained by anti‐CD200 as in a previous study (correlation P = 0.0042), but CD200R1 and CD200 were not correlated. Presence or absence of strong CD200 expression in the tumor did not correlate with metastasis, and a similar result was obtained with CD200R1. Conclusions This is the first report of CD200R1 expression by human epithelial tumor cells, and specifically, early‐stage human breast cancer cells. It is also the first report of CD200R1 expression by term placental villous trophoblasts. The potential biological significance of CD200R1 expression in non‐hematopoietic cells is discussed.